Regulating digital ecosystems: bridging the gap between competition policy and data protection - Kira, Beatriz; Sinha, Vikram; Srinivasan, Sharmadha (Industrial and corporate change, 2021)
Abstract Data collection and processing are at the core of rapidly growing business models, underpinning the activities of technology companies and acting as a source of market power. The key role played by data in the competitive dynamics of digital ecosystems has brought competition policy and data protection regulation closer together and raised important questions about the substantive relationship between these two branches of law. After identifying the specific ways in which data create and power digital ecosystems and examining the effects of digital privacy (or lack thereof) on consumer welfare, we compare the legal obligations imposed by competition policy and data protection regulation. We then map the interfaces between these two branches of law and critically assess the areas of substantive overlap between them. We show that while in the majority of situations there is an alignment of these two frameworks, opposite outcomes can sometimes be reached when competition and data protection rules are applied separately. We suggest that these two legal instruments should be considered as overlapping areas in a regulatory continuum to facilitate positive synergies and neutralize potential conflicts. We show that there is a significant scope for competition policy actors and institutions to substantially incorporate data protection considerations into their decisional practice and that this integration can inform and enhance the enforcement of competition law. We propose an integrated approach to more effectively regulate digital platform ecosystems, to support innovation, and to protect consumers and the competitive process.